Analysis Of Product Quality, Product Diversification, And Price On Purchasing Decisions Of Hni Hpai Business Centre Products In Medan 4 (A Case Study Of Muslims In Medan City) - Lubis, Khoirun Nisa; Nurbaiti, Nurbaiti; Atika, atika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of product quality, product diversification, and price on purchasing decisions of Business Centre HNI HPAI products in Medan City. The research background is based on the increasing need for halal products in Indonesia, especially in the herbal-based health product category. The research method uses a quantitative approach with a survey of 112 HNI HPAI consumers in Medan City. The independent variables consist of product quality, product diversification, and price, while the dependent variable is purchasing decision. Data were analyzed using multiple linear regression, with the results showing that all independent variables have a significant positive effect on purchasing decisions. The coefficient of determination of 67.2% indicates that these three variables explain most of the variation in purchasing decisions. This study concludes that product quality has the most dominant influence, followed by price and product diversification. The practical implication of this research is the need for companies to maintain product quality, increase product variety, and offer competitive prices to strengthen competitiveness in the halal herbal product market.